Answer:
8
Step-by-step explanation:
8 - 11 = -3 :)
Answer:
P'Q' is equal in length to PQ.
Step-by-step explanation:
Before rotation
P(-5, 3)
Q(-1, 3)
we get the length
L = √((-1-(-5))²+(3-3)²) = √((-4)²+(0)²) = 4
After rotation
P'(3, 5)
Q'(3, 1)
we get the length
L' = √((3-3)²+(1-5)²) = √((0)²+(-4)²) = 4
we can say that L = L' = 4
P'Q' is equal in length to PQ.
Answer:
Yo im taking the same thing lemme know what you get!!!
Step-by-step explanation:
It would be C, D, and E. when there is no line marked under the less than or greater than sign, it’ll be open circle
Answer:
the soulution is (5,10)
Step-by-step explanation: